1981
DOI: 10.1139/y81-029
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of migrating myoelectric complexes in human subjects: role of duodenal acidification and plasma motilin

Abstract: The hypothesis that acid, emptied intermittently from the stomach during fasting, might initiate the duodenal phase of the migrating motor complex was tested in normal human subjects. In addition, the relationship between plasma motilin concentrations and the initiation of migrating motor complexes was examined. Migrating complexes occurred spontaneously in the absence of acid in the duodenal bulb and in the presence of duodenal bulb neutralization with sodium bicarbonate. Thus duodenal bulb acidification is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1984
1984
2000
2000

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Measuring motilin response to a stimulus while ignoring its basal variation generates results of questionable significance, as we observed earlier in animals (22). Suboptimal experimental protocols used in earlier studies (6)(7)(8)(9)(10)(11) may possibly explain the controversial data then obtained. The postprandial increase of motilin we documented in man is not present in the dog, in which the ingestion of a meal abolishes motilin cyclical increases typical of the interdigestive period (3).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Measuring motilin response to a stimulus while ignoring its basal variation generates results of questionable significance, as we observed earlier in animals (22). Suboptimal experimental protocols used in earlier studies (6)(7)(8)(9)(10)(11) may possibly explain the controversial data then obtained. The postprandial increase of motilin we documented in man is not present in the dog, in which the ingestion of a meal abolishes motilin cyclical increases typical of the interdigestive period (3).…”
Section: Discussionmentioning
confidence: 92%
“…First, cyclic elevations in circulating motilin are present during the fasting state, coinciding with the phase 111 period of the MMC, and are abolished after feeding (3). Second, administration of exogenous synthetic canine motilin, at doses mimicking physiologic increases in the blood, in-(6), You et al (7), and Vantrappen et al (8) reported that the variations in endogenous circulating motilin were associated with the MMCs in man as in dog; however, these data could not be corroborated by Lux et al (9), Rees et al (lo), or Daniel et al (11).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that circulating motilin levels may rise as a result of intestinal muscle contraction expressing the peptide into the circulation during the m.m.c. (Daniel, Fox, Collins, Lewis, Meghji & Track, 1980;Sarna, Chey, Condon, Dodds, Myers & Chang, 1983). This proposed mechanism is difficult to accept in view of the observations of: peak motilin levels in dogs before, during or after m.m.c.…”
Section: Discussionmentioning
confidence: 97%
“…In humans, controversy exists as to the role of motilin. Ouyang and Cohen (26) report that motilin concentrations are closely associated with the onset of phase 3 interdigestive myoelectric activity, while Daniel et al (33) report that plasma motilin concentrations do not correlate well with the phases of myoelectric activity. Although we did not correlate motilin samples with propulsive phase 3 myoelectric activity, we observed insignificant changes in motilin concentrations following a CF or HOF meal.…”
Section: Resultsmentioning
confidence: 99%